2022
DOI: 10.1111/jonm.13725
|View full text |Cite
|
Sign up to set email alerts
|

Does empowerment enhance nurses' organizational commitment?

Abstract: Aim We examined whether psychological empowerment was significantly associated with the organizational commitment of licensed practical nurses. Background Healthcare organizations face unprecedented staffing challenges. This study provides insight into potential ways to ameliorate these issues. Methods In early 2010, we distributed a 45‐item questionnaire, based on established measures of psychological empowerment and organizational commitment, to the entire population of active, full‐time licensed practical n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…[7,8] Although nurses are crucial partners in the healthcare sector and among the frontline healthcare practitioners required to achieve effective healthcare-related programs, numerous challenges confronting hospitals today are frequently attributed to a lack of nurses' commitment and performance, given that nurse commitment is a critical issue in achieving overall hospital performance and pursuing the delivery of an effective healthcare system. [9][10][11][12] Commitment is strongly related to performance because committed nurses engage in more extra-role activities and behaviors such as creativity and innovation. [13] Nurses' dedication and performance have long been recognized as quality service determinants for patients admitted to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Although nurses are crucial partners in the healthcare sector and among the frontline healthcare practitioners required to achieve effective healthcare-related programs, numerous challenges confronting hospitals today are frequently attributed to a lack of nurses' commitment and performance, given that nurse commitment is a critical issue in achieving overall hospital performance and pursuing the delivery of an effective healthcare system. [9][10][11][12] Commitment is strongly related to performance because committed nurses engage in more extra-role activities and behaviors such as creativity and innovation. [13] Nurses' dedication and performance have long been recognized as quality service determinants for patients admitted to hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Chinese study by Hua et al [51] revealed that nurse managers who adopt Te fndings of the present study showed that psychological empowerment has a positive and signifcant impact on OCBs among nurses, supporting H3. Tis may be due to psychological empowerment is associated with higher levels of job satisfaction and organizational commitment among nurses, which further encourages them to exhibit OCBs as a form of positive citizenship behavior that enhances the overall efectiveness and success of the organization [53,54]. Our fndings are supported by the study of Turnipseed and VandeWaa [55] that was carried out among nurses in a medium-size urban general hospital and revealed that there are diferential relationships between the dimensions of psychological empowerment and the dimensions of OCBs.…”
Section: Discussionmentioning
confidence: 99%